ANALYSIS OF THE BIPA READING-SPEECH LEARNING MODEL BASED ON THE THEMATIC APPROACH OF INDONESIAN LOCAL WISDOM FOR GRADE 7 STUDENTS - Agus Setiyaningsih; Ida Widia; Mochamad Whilky Rizkyanfi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Teaching Indonesian as a Foreign Language (BIPA) should be designed to be contextual and communicative to effectively address learners' needs in language skills, particularly reading and speaking. This study aims to develop a thematic-based learning model that integrates local Indonesian wisdom to enhance reading and speaking skills among Grade 7 students. The research employed a development research method following the Dick and Carey instructional design model. Data were collected through observation, interviews, questionnaires, and language skill tests. The results indicated that the model was effective in improving students' reading comprehension, speaking confidence, and interest in Indonesian cultural content. There was a significant increase in students' average scores after the implementation of the model. Thus, integrating thematic content and local cultural values into BIPA learning proved to be an effective strategy to enhance students' language skills while fostering meaningful appreciation of Indonesian culture.